2020
DOI: 10.3390/ijerph17062022
|View full text |Cite
|
Sign up to set email alerts
|

Slums, Space, and State of Health—A Link between Settlement Morphology and Health Data

Abstract: Approximately 1 billion slum dwellers worldwide are exposed to increased health risks due to their spatial environment. Recent studies have therefore called for the spatial environment to be introduced as a separate dimension in medical studies. Hence, this study investigates how and on which spatial scale relationships between the settlement morphology and the health status of the inhabitants can be identified. To this end, we summarize the current literature on the identification of slums from a geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 130 publications
0
23
0
Order By: Relevance
“…Deprived areas are defined by social, environmental, and ecological risks to health and well-being such as lack of legal access to land, social amenities such as access to schools and health centers, or basic infrastructure such as roads and sewer lines (Table 1). Living in a deprived area can increase the incidence of disease via exposure to animal vectors and crowding of buildings, injuries such as fire, vulnerability to extreme weather events, higher incidence of crime, and physical and social barriers to services (Ezeh et al 2017;Friesen et al 2020). The "slum household" definition reflects household-level poverty, which poses unique risks such as crowding within the home and economic barriers to services.…”
Section: Need For An Integrated Deprived Area Mapping System (Ideamaps)mentioning
confidence: 99%
“…Deprived areas are defined by social, environmental, and ecological risks to health and well-being such as lack of legal access to land, social amenities such as access to schools and health centers, or basic infrastructure such as roads and sewer lines (Table 1). Living in a deprived area can increase the incidence of disease via exposure to animal vectors and crowding of buildings, injuries such as fire, vulnerability to extreme weather events, higher incidence of crime, and physical and social barriers to services (Ezeh et al 2017;Friesen et al 2020). The "slum household" definition reflects household-level poverty, which poses unique risks such as crowding within the home and economic barriers to services.…”
Section: Need For An Integrated Deprived Area Mapping System (Ideamaps)mentioning
confidence: 99%
“…Recent, largescale reviews showed that our knowledge of the health of slum inhabitants is very limited [ 16 , 19 ]. What we know is mostly limited to individual regions, such as Nairobi and Kenya [ 20 ]. These findings are confirmed when researching current measures to determine the extent to which countries are taking measures to protect their vulnerable populations.…”
Section: What We Do Not Knowmentioning
confidence: 99%
“…Detailed comparative research on slum dwellers’ state of health. It is necessary to investigate what commonalities and differences in the health status of slum dwellers exist [ 20 ]. This refers both to the differences within a city between groups living in formal and informal settlements [ 24 ], which was done for HIV in South Africa [ 25 ], and to the differences across slums in different global regions.…”
Section: What We Should Knowmentioning
confidence: 99%
“…The size of most slums is between 10 −3 km 2 and 10 −1 km 2 and thus shows no dependence on the total number of morphological slums within the city. This information can be used as typical scale in other scientific domains such as infrastructural planning [8] or epidemiological analyses [9,10].…”
Section: Introductionmentioning
confidence: 99%